Moderating role of green innovation between sustainability strategies and firm performance in Tanzania - Hellena Mohamedy Mushi (Cogent Business & Management)
This journal article investigates the moderating role of green innovation in the relationship between sustainability strategies and firm performance within the manufacturing sector in Tanzania. With increasing global emphasis on environmental sustainability, this study seeks to understand how green practices influence the performance of firms striving for a competitive edge. A quantitative research design was adopted, with data collected from a structured questionnaire distributed and 340 responses received for analysis from mid-level and senior managers across 10 public and private manufacturing companies in Tanzania. The study utilized SMART PLS 4 for data analysis, testing the proposed hypotheses grounded in Resource-Based Theory (RBT). The findings reveal a significant positive relationship between sustainability strategies and firm performance, highlighting the importance of integrating sustainable practices into business operations. However, while green innovation directly influences firm performance, it does not significantly moderate the relationship between sustainability strategies and performance outcomes. These findings suggest that manufacturing firms in Tanzania can improve performance by adopting sustainable strategies, even in the absence of a moderating effect from green innovation. The study concludes by offering actionable recommendations for industry practitioners and policymakers to encourage sustainable business practices, thereby supporting the broader goal of sustainable development in Tanzania.